Independence Day Effect in the Stock Price of ASEAN State-Owned Enterprises - Setiawan, Marvella Justia; Murtaqi, Isrochmani (Journal of Business and Management, 2016)
Abstract. Holiday effect is an anomaly on stock returns related to public holidays. This findings oppose Efficient Market Hypothesis directly as it proves that abnormal return presence. Lakonishok and Schmidt (1998) defined public holiday as days when market is closed, such as Labor Day, Presidentâ€™s Day, Memorial Day, Independence Day, Thanksgiving, New Year, Good Friday, and Christmas. The study reported that 30% up to 50% more return can be gained in holiday season compared to non-holiday season.Â Keyword(s): Holiday Effect, Independence Day, ASEAN